A proposed induction program for new teachers in the Division of Pasay City - Espiritu, Bienvenida B. 1922- ([s.n.], 1971)
Aware of the importance and necessity of having an induction program geared towards the needs of new teachers, it was the purpose of this study to propose a program of induction which would consider the difficulties met by new mentors in Pasay City. With the conclusions and findings of the study as bases, the writer proposed an induction program for new teachers in Pasay City which considers the principles for good induction programs.